Alternative Ways to Control Fertility in Indonesia - Dahroni, D (Forum Geografi, 1990)
An effort for reducing fertility in developing countries like Indonesia, is a real initiative to decrease the population growth rate. The succes of family planning programme in reducing fertility of Indonesia, has been confessed by UNO, and as a result, president Suharto has been rewarded a United Nation Population Award. Besides it is considered to make another effort beyond family planning programmes, among other things are: to raise age of marriage, future cousciousness, moral, and health education. Those programmes can be carried out through formal and informal education as well. The aim of family planning programme is to create a small family of lawful marriage and have heredity. In order to have a quantity and a good quality of heredity we are likely to become, then, there should be a planning of giving birth. Nevertheless, campaign motivation to raise age of marriage for young generation in rural as well as in urban, is one of the main efforts to reduce fertility rates.